Fuzzy Mamdani Pada Tanaman Tomat Hidroponik - Budi Prasetya; Aries Boedi Setiawan; Basitha Febrinda Hidayatulail (Muhammadiyah University, Sidoarjo, 2019)
Tomato plants are one of the many agricultural commodities needed by the community. Most farmers grow tomatoes in conventional ways in the fields, fields or plantations without the control and measurement relying on experience and habitual factors, so the need for pH and temperature of the planting space of tomato plants cannot be given according to their needs, while the pH requirements of tomato plants range 6.5 and the planting room temperature is 28 °C, and soil moisture is 70%, using the hydroponic planting method which is automatically controlled by the Arduino-based microcontroller with the application of fuzzy mamdani making it easy to do pH setting of planting media using soil pH sensor as input and temperature of planting room using LM35 temperature sensor, and soil moisture sensor using humidity sensor fc28, as the system output fan and selenoid valve are used. To find out plant nutrition, one of the indicators is the pH value of soil media, room temperature and humidity of the planting medium.